(untitled) (Bangladesh Journal of Urology, 2020)
Background: Prostate cancer is the most common cancer in men. The most common prostate cancer test is the prostate-specific antigen (PSA) test. This is a simple blood test that measures the presence of prostate-specific antigen circulating in bloodstream. This test is usually the first step in any prostate cancer diagnosis. Objective: To detect the occurrence of prostate cancer at different level of serum PSA level between 2.5ng/ml and 4ng/ml. Method: This hospital based cross sectional analytical study was conducted between the periods of January 2012 to April 2013. A total of 30 patients with features of lower urinary tract symptoms with enlarged prostate attending to the Department of Urology, National Institute of Kidney Diseases & Urology (NIKDU), Sher-E-Bangla Nagar, Dhaka were purposively selected as study population by taking the permission of ethical committee. Patients more than 50 years old with lower urinary tract symptoms at S. PSA level 2.5 - 4 ng/ml and enlarged prostate in DRE were selected as study population. Patients with bleeding disorder, anorectal pathology, active UTI or prostatitis or urethral stricture were excluded from this study. DRE was done to see the size, consistency and nodularity of prostate. Those who had enlarged prostate found on DRE, they were sent for biopsy multi parametric MRI (MPMRI) & Prostate Imaging Reporting and Data system (PIRAD) score may be applied. Result: The mean age of the patients was 66.87±10.13 years with a range of 52-90 years. Among 30 patients 10 (33.3%) were in the age group of 51-60 years, 10 (33.3%) were in the age group of 61 - 70 years, 5 (16.7%) were in the age group of 71 - 80 years and 5 (16.7%) were in the age group >80 years. Among 30 patients 4 (13.3%) had malignant lesion and 26 (86.7%) had benign lesion. Mean serum PSA level among the patients with histopathological findings benign and malignant were 3.34±0.51 and 3.47±0.43 ng/ml respectively. Out of 4 patients with malignant lesion, 1(25.0%) had serum PSA level within 2.50-2.99 ng/ml, another 1(25.0%) had 3.00-3.49 ng/ml and 2(50.0%) had serum PSA level within 3.50-4.00 ng/ml. There is no statistically significant difference observed in serum PSA level among the patients with histopathological findings benign and malignant (P>0.05). Conclusion: For early diagnosis of prostate cancer cut-off value of serum PSA of 2.5 ng/ ml may be used as an indication for prostate biopsy. Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.85-89